RENEWABLE ENERGY ADOPTION FOR ENERGY COMPLEMENTARY: APPLICATION OF OFFSHORE WIND TURBINES IN SABAH, MALAYSIA. - Salleh, NurFarahin; Chew, Boon Cheong; Hamid, Syaiful Rizal (Journal of Technology Management and Business, 2016)
Nowadays, the world electricity requirements are increasing at an alarming rate and the power demand is running ahead of supply. It is widely recognized that the fossil fuels such as coal, petroleum and natural gas are presently being used for electricity. Therefore, in future it may not be sufficient to keep pace with ever increasing demand of the electrical energy of the world. The renewable energy can provide clean sources of energy which is reliable and secure to society. This paper analyzed renewable energy adoption, focusing on offshore wind turbines. In this case study, Labuan, Sabah has been selected as a location to install the offshore wind turbines because of the geographical advantage of the South China Sea. The technology is expected to provide great power energy with the least environment impact and high sustainability as it is located within the windy area with no terrain features, buildings or other obstruction. This study used qualitative methods for both data collection and data analysis. This study proved that the application of offshore wind turbines in the South China Sea, Sabah produced the complementary energy to fossil fuels and resulted in the acceptance of Sabah residents towards the installation of the offshore wind turbines. Hence, the offshore wind turbines might become one of the main energy sources in Sabah. The application of the offshore wind turbines to Sabah residential area develops a lot of benefit and support the Malaysian government goal which is to be more competitive in renewable energy generation while sustaining national economic growth.Â